Case Report: Aspiration Pneumonitis as a Rare Complication Following Hydrogen Peroxide Intoxication - Putri, Maulinda; Suhartomi; OK Yulizal; Syarifah, Siti (Jurnal Kedokteran Meditek, 2025)
Introduction: Suicide rates continue to rise globally, with self-poisoning being a common method in some developing countries. This report reported a case of hydrogen peroxide ingestion leading to aspiration pneumonitis, a less-discussed complication compared to gastrointestinal toxicity. Case Illustration: A 41-year-old woman presented to the emergency unit 8 hours post-ingestion of a hydrogen peroxide-based toilet cleaner. Symptoms included vomiting, hoarseness, faintness, and frothing at the mouth. The physical examination revealed dyspnea, irritability, a cleaning solution odor in the oral cavity, rhonchi in the middle and lower lung fields, epigastric tenderness, and increased bowel sounds. Gastric lavage with 200 mL of saline was performed, and activated charcoal and sucralfate syrup were administered via a nasogastric tube. The patient had previously received ranitidine at another facility and was also treated with omeprazole and ondansetron. Laboratory results showed leukocytosis, and a chest x-ray indicated bilateral lung infiltration and increased broncho-vascular pattern. Discussion: Early and proper intervention by trained healthcare professionals, combined with preventive measures such as positioning the patient in a semi-upright position and avoiding emetogenic liquids, is essential. Conclusion: This case showed the importance of prompt management involving gastric lavage, mucosal protection, acid suppression, and absorption inhibition. Nonetheless, respiratory complications, such as aspiration pneumonitis, remain challenging to prevent.